Compressive, shear, and fracture behavior of CNT reinforced Al matrix composites manufactured by severe plastic deformation. (15th September 2016) - Zare, Hassan; Jahedi, Mohammad; Toroghinejad, Mohammad Reza; Meratian, Mahmoud; Knezevic, Marko
Abstract: In this work, carbon nanotubes (CNTs) reinforced aluminum (Al) matrix composites are synthesized using Bc equal-channel angular extrusion (ECAP) route and their mechanical behavior is examined under compression and shear deformation. The results show that at room temperature, eight ECAP passes are necessary to achieve the density of the composite where the effect of CNTs in enhancing the mechanical properties become significant. Samples of pure Al are also processed under the same ECAP conditions, and their properties are further examined to facilitate the comparison. The well-densified composites with only 2 vol.% of CNTs exhibit an approximately 30% increase in yield strength compared to the pure Al samples. Microstructure data in terms of porosity volume fraction, crystallite size, and dislocation density, along with the residual lattice strain measurements, are used to explain the observed improvements in strength. As measured by X-ray diffraction (XRD), higher levels of dislocation density, smaller crystallite sizes, and larger residual lattice strains are present in Al-CNT than in pure Al samples. Finally, fractographic analysis using scanning electron microscopy is performed revealing that the fracture surfaces of the composite exhibit a more brittle behavior than pure Al samples. Graphical abstract: Highlights: CNT reinforced Al composites of high homogeneity are synthesized using ECAP. Porosity, dislocation density, crystallite sizes, and lattice strains are characterized. Fine-grained CNT-Al composites exhibit 30% increase in strength over fine-grained Al. Fracture surface of the composite exhibits characteristics of brittle behavior.